Understanding the impact of triazoles on female fertility and embryo development: Mechanisms and implications - Sonal Sharma; Geeta Pandey (Toxicology Reports)
Triazoles are among the most widely used fungicides that were launched in 1980s and are one of the most important pesticide groups used in agriculture as plant growth regulators and stress protectors. Triazoles are also frequently used in the pharmaceutical industry to treat fungal and bacterial infections as well as to treat and prevent some forms of pneumonia. Humans are normally exposed to triazoles through food, water, and medications, which raises concerns about their potential adverse effects on health. Therefore, this review was planned to examine the impact of triazole fungicides on female fertility, as well as their teratogenic and embryotoxic effects. Various search engines such as PubMed, Google Scholar, Elsevier, IEEE were used to search the relevant articles published between 2006 and 2024 using the following keywords: ''azoles,'' ''female infertility,'' ''reproductive toxicity,'' ''teratogenicity,'' ''triazoles,'' and ''embryo toxicity.'' The findings suggest that triazoles might negatively affect female fertility and embryonic development through multiple mechanisms including inhibition or interference with key enzymes such as CYP17A1 and CYP19A1 (aromatase) involved in steroid hormone synthesis, endocrine disruption, oxidative stress, disruption of signaling pathways, and apoptosis. This review consolidates current knowledge on the teratogenic and embryotoxic properties of triazole fungicides, providing a comprehensive understanding of their health implications and addressing critical research gaps.